Differential Effect of Aluminium on Enzymes of Nitrogen Assimilation in Excised Bean Leaf Segments - Gupta, Priyanka; Sarengthem, Juliana; Dhamgaye, Sonal; Gadre, Rekha (Scientific Research Publishing, 2016)
Aluminium is a potent toxicant in acidic soils. The present study was taken up to analyze the effects of Al on enzymes of nitrogen assimilation in excised bean (Phaseolus vulgaris) leaf segments so as to gain an insight of the mechanism involved. Supply of 0.001 to 0.1 mM AlCl3 to excised bean leaf segments affected the in vivo nitrate reductase activity differently in the presence of various inorganic nitrogenous compounds, being inhibited with 5 mM ammonium nitrate and 10 mM ammonium chloride but enhanced with 10 mM potassium nitrate. Al effect with 50 mM KNO3 varied with time, showing an increased activity at shorter duration, but decreased at longer duration. Al effect on in vivo NRA was dependent upon the nitrate concentration, thus, inhibiting it at 0, 1 and 50 mM KNO3, while increasing at 2 and 10 mM. Further, saturating and non-saturating effects were observed in the absence and presence of Al. Al supply influenced the in vitro NRA also, being increased at 10 mM, but decreased at 50 mM KNO3. Supply of Al to excised leaf segments substantially inhibited the glutamate dehydrogenase activity in the absence as well as presence of 5 mM NH4NO3 but increased the glutamate synthase activity. Inhibition of specific glutamate dehydrogenase activity by Al supply was also observed. However, specific glutamate synthase activity was increased in the presence of NH4NO3 only. The experiments demonstrated that effect of supply of aluminium on in vivo nitrate reductase activity depended upon nitrogenous source as well as nitrate concentration and it exerted reciprocal regulation of glutamate dehydrogenase and glutamate synthase activities, which depended upon N supply too.
Keywords: Aluminium Effect; Glutamate Dehydrogenase; Glutamate Synthase; Nitrate Reductase; Bean Leaves; Phaseolus vulgaris